Optimized graph-cut approach for the screen-line traffic counting location problem: An exact and efficient solution method - Sase, Ruri; Sugiura, Satoshi; Chen, Anthony (Expert systems with applications, 2025)
•A novel approach as Cut Optimization Problem (COP) for screen-line counter location problem (SLTCLP) based on graph cut without path enumeration.•Exact solution formulation without any heuristic algorithms.•Providing an exact solution within small computation cost even in the large networks.•Illustration the properties of SLTCLP solution based on graph-cut structure on characteristic of road networks. Observed traffic data are widely recognized as an essential source of information for monitoring, evaluating, and planning transportation systems. The traffic sensor location problem is aimed at determining the optimal locations for collecting the most informative partial observations. This study focuses on the screen-line traffic counting location problem (SLTCLP). Screen lines are commonly used to validate traffic assignment results because of the ease of interpreting their positions. Therefore, addressing this problem is valuable for effective transportation management. Conventional solutions to this problem are based on path enumeration, which is computationally expensive and difficult to implement for large-scale transportation networks. Thus, we establish an exact and efficient solution method for the SLTCLP, using the concept of cut in graph theory and formulating the problem as the “cut optimization problem.” The proposed method is applied to different types of network instances, including a large network, and its performance and effectiveness are evaluated.